Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.4 Exponential Functions - 2.4 Exercises - Page 86: 17



Work Step by Step

In the exponential functions a given value of x leads to exactly one value of $a^x$, thus we can rewrite the equation: $4^x=8^{x+1}$ $4^x = (2^2)^x= 2^{2x}$ $8^{x+1}= (2^3)^{x+1}= 2^{3\times (x+1)}=2^{3x+3}$ So, $2^{2x}=2^{3x+3}$. $2x=3x+3$ $-3=x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.